Some Historical Realia in Russian and Romanian: Lexical and Phraseological Correspondences - Daniela GHELTOFAN (Scientific Bulletin of the Politehnica University of Timişoara: Transactions on Modern Languages, 2020)
In this paper, we advance a set of correspondences of Russian realia words (i.e. culture-specific items) in Romanian. These historical words will be part of a dictionary, together with about 200 realia units, arranged by categories: ethnographic realia, sociopolitical and administrative realia, geographical realia, and onomastic realia, addressed to young translators from Russian to Romanian, as well as to those interested in Russian culture.